SP2.1.16Prognostic significance of Drivers at Work and Learning Styles in surgical training. (28th October 2021) - Mellor, Katie; Hopkins, Luke; James, Osian P; Luton, Oliver; Egan, Richard J; Lewis, Wyn G
Abstract: Aims: Drivers at Work (DW) and Learning Styles (LS) refer to a range of contentious theories that aim to account for differences in career progression, yet seldom feature in training assessment. This study aimed to quantify the influence of Core Surgical Trainees' (CST) DW and LS on career progression. Methods: Kolb LS inventories were distributed to 168 CSTs during five consecutive induction boot camps in a single Statutory Education Body. Primary outcome measures were MRCS and National Training Number (NTN) success. Results: Of 108 responses received (response rate 64.3%), 64.8% were male and 35.2% female (p = 0.003). The spectrum of DW was: Please People (25%), Be Perfect (21.3%), Hurry Up (18.5%), Be Strong (13.9%), and Try Hard (0%, p < 0.001). DW was either unequivocal or not provided by 23 CSTs (21.3%). The spectrum of LS was: Converging (34.3%), Accommodating (28.7%), Diverging (23.1%), and Assimilating (13.9%, p = 0.021). MRCS success was not associated with DW (p = 0.703) or LS (p = 0.598). Men were more likely to have Converging LS (29/70, 41.4%), and women Diverging LS (15/38, 39.5%, p = 0.018) and to have team-based LS (Accommodating / Diverging, 26/38 vs. 30/70, p = 0.010). NTN success was associated with LS (p = 0.038) with Convergers achieving most NTNs (65.4%). Conclusions: LS are associated with important differences in career progression with Converging LS three-fold more likely to achieve NTNs than Diverging LS.